2008
DOI: 10.1037/0096-1523.34.4.884
|View full text |Cite
|
Sign up to set email alerts
|

Are attractive men's faces masculine or feminine? The importance of type of facial stimuli.

Abstract: The authors investigated whether differences in facial stimuli could explain the inconsistencies in the facial attractiveness literature regarding whether adults prefer more masculine- or more feminine-looking male faces. Their results demonstrated that use of a female average to dimorphically transform a male facial average produced stimuli that did not accurately reflect the relationship between masculinity and attractiveness. In contrast, use of averages of masculine males and averages of feminine males pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
90
2
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(100 citation statements)
references
References 53 publications
6
90
2
2
Order By: Relevance
“…However, subsequent research on women's preferences for male masculinity has shown considerable variation. While this variation is sometimes attributed to differences in methodology (Rennels, Bronstad, & Langlois, 2008;Rhodes, 2006), even studies using the same computer-graphic methods have variously observed general preferences for masculinity Johnston, Hagel, Franklin, Fink, & Grammer, 2001;Little, Cohen, Jones, & Belsky, 2007;, general preferences for femininity (Little, Burt, PentonVoak, & Perrett, 2001;Little, Jones, PentonVoak, Burt, & Perrett, 2002;Penton-Voak et al, 1999Perrett et al, 1998;Rhodes et al, 2000;Welling et al, 2007;, Study 1), and no significant preference for masculinity or femininity (Cornwell et al, 2004;Swaddle & Riersen, 2002;Welling et al, 2008, Study 2).…”
Section: Sex Differences In Face Preferences Female Femininity Versusmentioning
confidence: 94%
See 2 more Smart Citations
“…However, subsequent research on women's preferences for male masculinity has shown considerable variation. While this variation is sometimes attributed to differences in methodology (Rennels, Bronstad, & Langlois, 2008;Rhodes, 2006), even studies using the same computer-graphic methods have variously observed general preferences for masculinity Johnston, Hagel, Franklin, Fink, & Grammer, 2001;Little, Cohen, Jones, & Belsky, 2007;, general preferences for femininity (Little, Burt, PentonVoak, & Perrett, 2001;Little, Jones, PentonVoak, Burt, & Perrett, 2002;Penton-Voak et al, 1999Perrett et al, 1998;Rhodes et al, 2000;Welling et al, 2007;, Study 1), and no significant preference for masculinity or femininity (Cornwell et al, 2004;Swaddle & Riersen, 2002;Welling et al, 2008, Study 2).…”
Section: Sex Differences In Face Preferences Female Femininity Versusmentioning
confidence: 94%
“…Methodological issues are frequently cited as possible sources of variable general masculinity preferences (Rennels et al, 2008;Rhodes, 2006;Scott et al, 2013). However, several lines of evidence suggest that methodological differences between studies contribute little to reports of systematic variation in women's masculinity preferences.…”
Section: Measuring Masculinity Preferencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Las Visión y olfato en las evaluaciones de atractivo pruebas directas realizadas para comprobar esta hipótesis muestran que el grado de parecido de un rostro al promedio es suficiente para predecir su atractivo, sin importar su grado de simetría (DeBruine, Jones, Unger, Little & Feinberg, 2007;Rennels, Bronstad & Langlois, 2008). La masculinidad es el ras go que mejor predice el atractivo en un rostro de hombre.…”
Section: Atractivo Facialunclassified
“…La masculinidad es el ras go que mejor predice el atractivo en un rostro de hombre. Sin embargo, también se encontró que los extremos en masculinidad no son agradables (Rennels et al, 2008).…”
Section: Atractivo Facialunclassified